SINGARAJA MEFLOPORT: BANDARA DENGAN KONSEP MEGAFLOAT SEBAGAI SOLUSI PEMERATAAN PEMBANGUNAN BALI UTARA - Mahendra, I Nengah Adi; Wiryawan, Bagus Ngurah Alit Putra; Sucitra, I Gusti Ngurah Bayu; Perdana, Gde Parie (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Tourism is the main economic activity that is developed on the Bali Island. Ngurah Rai International Airport is the main gate of economic activity of tourism in Bali and Indonesia. Rapid passenger growth, providing ideal conditions impact on the airport. Efforts were made to overcome this problem is the construction of a new airport in the north of Bali. In addition, the construction of the airport was used as an equal opportunity in economic development in Bali. Singaraja Mefloport is the concept of a floating airport that also has the advantage of modern and environmentally maid. This concept is very feasible to be developed in North Bali because (1) no require land acquisition on land, (2) is not blocked by the hills of North Bali is very near to the North Sea, and (3) no impact on the environment because it does not do reclamation process. Singaraja Mefloport consists of four components, namely a floating Pontoon placed wide structure, foundation reinforcement, bridge access from the land to the floating region, and breakwaters. The main components of a floating structure with a protective are precast slab, deck framing, column and diagonal support decks, buoyancy space, and the anchorage system. The concept is expected to remain Singaraja Mefloport can protect marine life and the ecosystem as well as through the airport engineering was able to create a comfortable and friendly environment.Keywords: Singaraja Mefloport, Airport, Megafloat